ANALISIS MEKANISME AUDIT PEMBIAYAAN PADA BANK SYARIAH - Muhammad Lathief Ilhamy Nasution (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
The development of Sharia Bank depends on the role of its customers which regularly rises in terms of its number whether it shows less significance. Sharia Bank runs its business under the principle of sharia making it should be relevant and stick to the sharia itself. The operation is closely monitored by The Board of Sharia Monitoring (DPS) tasked to monitor and suggest to the management in ensuring that the bank operates under strict sharia rule so as to convince the customers that they are also stick to it. By the end of each year, DPS releases its internal report along with external auditor report. These reports are useful for financial report users who are stick to the religious values as a guarantee and convincing them that all financial transaction of the bank has operated under the sharia law. The examination is conducted by an external auditor who are qualified in managing accounting. This may rise a question whether it is relevant that “conventional” auditor examined and generating examination report for an Islamic organization (including for Sharia Bank) despite its professionalism and competence.